Disturbed flow in a patient-specific arteriovenous fistula for hemodialysis: Multidirectional and reciprocating near-wall flow patterns - Ene-Iordache, Bogdan; Semperboni, Cristina; Dubini, Gabriele; Remuzzi, Andrea (Journal of biomechanics, 2015)
Actual surgical creation of vascular access has unacceptable failure rates of which stenosis formation is a major cause. We have shown previously in idealized models of side-to-end arteriovenous fistula that disturbed flow, a near-wall hemodynamic condition characterized by low and oscillating fluid shear stress, develops in focal points that corresponds closely to the sites of future stenosis. Our present study was aimed at investigating whether disturbed flow occurs in patient-specific fistulae, too. We performed an image-based computational fluid dynamics study within a realistic model of wrist side-to-end anastomosis fistula at six weeks post-surgery, with subject-specific blood rheology and boundary conditions. We then categorized disturbed flow by means of established hemodynamic wall parameters. The numerical analysis revealed laminar flow within the arterial limbs and a complex flow field in the swing segment, featuring turbulent eddies leading to high frequency oscillation of the wall shear stress vectors. Multidirectional disturbed flow developed on the anastomosis floor and on the whole swing segment. Reciprocating disturbed flow zones were found on the distal artery near the floor and on the inner wall of the swing segment. We have found that both multidirectional and reciprocating disturbed flow develop on the inner side of the swing segment in a patient-specific side-to-end fistula used for vascular access after six weeks post-operatively. This has obvious implications for elucidating the hemodynamic forces involved in the initiation of venous wall thickening in vascular access.